Are portrait artists superior face recognizers? Limited impact of adult experience on face recognition ability. - Jeremy Tree (Journal of Experimental Psychology: Human Perception and Performance, 2017)
Across two studies, we asked whether extensive experience in portrait art is associated with face recognition ability. In Study 1, 64 students completed a standardized face recognition test before and after completing a year-long art course that included substantial portraiture training. We found no evidence of an improvement in face recognition after training over and above what would be expected by practice alone. In Study 2, we investigated the possibility that more extensive experience might be needed for such advantages to emerge, by testing a cohort of expert portrait artists (N = 28), all of whom had many years of experience. In addition to memory for faces, we also explored memory for abstract art and for words in a paired-associate recognition test. The expert portrait artists performed similarly to a large, normative comparison sample on memory for faces and words, but showed a small advantage for abstract art. Taken together, our results converge with existing literature to suggest that there is relatively little plasticity in face recognition in adulthood, at which point our substantial everyday experience with faces may have pushed us to the limits of our capabilities.